Medkulturna vzgoja in izobraževanje v vrtcu in v prvem triletju osnovne šole - Mojca Vah Jevšnik (Journal of Elementary Education, 2010)
Intercultural education in kindergarten and the first three years of primary school. An intercultural dialogue is an open and respectful exchange of views between individuals and groups with different ethnic backgrounds on the basis of mutual understanding and respect. Successful implementation of an intercultural dialogue is the basis for the development of inclusive societies, which strive towards integration and social cohesion. Such societies refuse the marginalization of vulnerable social groups. At the same time, it contributes to the fight against prejudice and stereotyping in public life and political discourse. The article addresses the importance of introducing intercultural education to children in kindergarten and the early years of elementary school. This is done by integrating the content of various activities and subjects and offering guidelines for its implementation.